Evaluation of Functional Instant Coffee and Chocolate Powders for Targeting Gout-Related Oxidative Stress and Inflammation - Nurul Nasuha Mohd Rosli,; Angzzas Sari Mohd Kassim, (Progress in Engineering Application and Technology, 2026)
Gout is a metabolic disorder associated with hyperuricemia, oxidative stress and inflammatory processes, leading to growing interest in functional food–based management strategies. This study reports investigation of the antioxidant and anti-inflammatory activities, as well as the physicochemical quality and safety, of instant coffee and chocolate powder formulations enriched with selected herbal extracts, turmeric (Curcuma longa), temulawak (Curcuma xanthorrhiza) and ginger (Zingiber officinale) supplied by an industry partner. Antioxidant capacity of both raw herbal extracts and formulated products was evaluated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging and ferric reducing antioxidant power (FRAP) assays, together with determination of total phenolic content (TPC). Anti-inflammatory activity was assessed using an in vitro protein denaturation assay. Product quality and safety were examined through solubility testing, moisture content determination and heavy metal analysis (lead, cadmium and arsenic). The herbal-enriched formulations demonstrated significantly enhanced antioxidant and anti-inflammatory activities relative to non-enriched controls. DPPH radical scavenging activity ranged from 44.8–86.5% for the chocolate formulation and 94.6–98.4% for the coffee formulation, while FRAP values ranged from 0.105–0.144 mg AAE/ml and 0.143–0.178 mg AAE/ml, respectively. Concentrations of all analysed heavy metals were within permissible regulatory limits. These findings indicate that herbal-enriched instant coffee and chocolate powders exhibit favourable functional properties and support their potential application as functional beverages for mitigating oxidative stress and inflammation associated with gout.